ECONOMIC POTENTIAL ANALYSIS RENGKAM ON BATAM ISLAND - Denny Ammary Ramadhan; Hanafi Siregar; Ramon Zamora (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
: The marine and fisheries resources sector is one of the potentials that is widely utilized by coastal communities who mostly work as fishermen. The lives of fishermen who depend on natural conditions can be proven by the income of fishermen who increase during the fish season. The off-season causes the intensity of fishing to decrease, thus the amount of income received by fishermen is certainly drastically reduced. Collecting rengkam can be a solution for fishermen who have obstacles in catching fish. This profession switch provides benefits and improves welfare and makes coastal communities have choices to make a living. Rengkam has the potential to improve the welfare of coastal communities, especially during the season when fish are difficult to obtain, while it has consequences for ecosystem changes that cannot be ruled out. This study aims to scientifically examine the social and economic potential of rengkam exploration and review the environmental impacts of exploration activities and determine strategies that can be carried out to maximize social and economic potential and minimize the possibility of environmental impacts. This research uses a qualitative approach. Qualitative approach was conducted through in-depth interviews and field observations (primary data collection). This research was conducted at one location of the rengkam exploration center, Pecong Island, with the subjects involved in the research process being the community and SKPD at the research location. Measurements using survey instruments, interviews, observations and literature review. Qualitative data collected was analyzed using the Narrative Analysis method of important data not only related to context, but also time, place, specifications, experience, and suggestions for consideration.